Evaluasi Penerapan Keuangan Berkelanjutan Berdasarkan POJK Nomor 51/POJK.03/2017 (Studi Kasus pada Bank Sumsel Babel) - Oka, Nabila Khuriah Dwi; Hermawan, Ancella Anitawati (Politeknik Ganesha Medan, 2025)
This research aims to evaluate the implementation of sustainable finance at Bank Sumsel Babel, how the implementation process is, and identify obstacles and factors that cause the implementation to succeed/fail. In conducting this evaluation, criteria from POJK No.51/POJK.03/2017 are used, especially the Technical Guidelines for Banks regarding the Implementation of POJK 51 issued by OJK, as well as criteria from research conducted by Vigfússon et al. (2021). The research instruments used are literature review and interviews, and the data analysis techniques in this study are content analysis and descriptive analysis. The results showed that Bank Sumsel Babel had implemented sustainable finance at the initial implementation stage. However, there are still several stages that have not yet been implemented by Bank Sumsel Babel, such as adjusting SPO in the BKI Division, developing or innovating sustainable finance products/services, initiating portfolios, and external education. In addition, Bank Sumsel Babel has not fully succeeded in implementing sustainable finance based on POJK 51 of 2017, where Bank Sumsel Babel still has not internalized key principles such as responsible investment, sustainable business strategies and practices, and social and environmental risk management principles. Factors that hinder the implementation of sustainable finance at Bank Sumsel Babel are barriers from external parties (customers) and lack of resources. The factors that caused the unsuccessful implementation of sustainable finance at Bank Sumsel Babel are management style and the effect of implementation support, also the time frame and priorities set.